1972
DOI: 10.1136/pgmj.48.557.156
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine anaesthesia for burns surgery

Abstract: SummaryA study was set up to investigate whether the theoretical advantages ketamine offered as an anaesthetic in burns patients were real.Patients under 35 kg body weight were anaesthetized by an intermittent intramuscular technique and patients over this weight with an intravenous technique.The study showed that ketamine had distinct advantages, giving cardiovascular stability and avoiding intubation. It was especially useful in the very ill patients. There were few complications during the study which we ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…demonstrated in 1972 that ketamine had distinct advantages, namely, superior cardiovascular stability profile and reduced respiratory depression when compared with other anesthetic agents. This study reported complications including emergence delirium or hallucinations, hypotension in one child (who responded to cortisone), and uncontrolled limb movements, more often seen in patients with epilepsy [20]. An article published in 1976 by Ward et al.…”
Section: Discussionmentioning
confidence: 81%
“…demonstrated in 1972 that ketamine had distinct advantages, namely, superior cardiovascular stability profile and reduced respiratory depression when compared with other anesthetic agents. This study reported complications including emergence delirium or hallucinations, hypotension in one child (who responded to cortisone), and uncontrolled limb movements, more often seen in patients with epilepsy [20]. An article published in 1976 by Ward et al.…”
Section: Discussionmentioning
confidence: 81%
“…(bolus) or 4-11 mg/kg administered i.m. (Sage and Laird, 1972;Sussman, 1974;Dachs and Innes, 1997;Weber et al, 2004;Green et al, 2011;Gao et al, 2016). Peak ketamine plasma concentrations of approximately 1200-2400 ng/ml, or 5-10 mM, are necessary to induce dissociative anesthesia (Little et al, 1972;Idvall et al, 1979;Grant et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…4 These symptoms are less frequent in children of less than 10 years old and seen commonly in elderly patients of fourth of fifth decades of life. 5 Beyond emergent reactions, ketamine produces a number of side effects that influence major body systems. The drug stimulates the cardiovascular system, producing increases in heart rate and blood pressure by 20%, immediately after injection and this effect may persist throughout the period of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The drug stimulates the cardiovascular system, producing increases in heart rate and blood pressure by 20%, immediately after injection and this effect may persist throughout the period of anaesthesia. 5,6 These effects are indirect and are most likely mediated by inhibition of both central and peripheral catecholamine reuptake. Ketamine has direct negative inotropic and vasodilating activity, but these effects usually are overwhelmed by the indirect sympathomimetic action.…”
Section: Discussionmentioning
confidence: 99%